Student Search: The Study of Ethics Educational Leadership Management - Suriyadi, Suriyadi; Sibuea, Bismar; Suardi, Suardi; Siahaan, Amiruddin; Nasution, Inom (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Student Search is often interpreted as "looking for students", while in the context of management, the term means examination or search of students. The "legal umbrella" regarding the application of student search in educational institutions in Indonesia is still not specifically regulated by the government, especially the ministry of education and culture. This study aims to analyze student search from the ethical point of view of educational leadership management. This research uses a qualitative approach with a literature study method. The sources of data and study analysis materials are based on relevant scientific literature, including books, articles, proceedings (national/international), and final projects (thesis, thesis, or dissertation). The results of this study indicate that student search still leaves confusion (polemic) in its application because until now there has been no regulation from the relevant ministry or government that specifically addresses the ethics of examination of students. This is because the Criminal Procedure Code only regulates the procedures for searching the public in general (not specifically on students), as well as in the Regulation of the Minister of Education and Culture Number 19 of 2007 concerning Education Management Standards which does not specifically contain the rules for student search. Furthermore, the regulation only concludes that school rules and regulations are entrusted to the principal with the consideration of the education board and school committee.